Chemical evaluation and In-vitro gas emission in mixed King Grass and Clitoria-ternatea silages - López-Garrido, Serafín Jacobo; Ramos-Ramos , Diego Arturo; Galicia-Jiménez, Mónica Marcela; Camacho-Escobar, Marco Antonio; Ávila-Serrano, Narciso Ysac; Ramirez-Bribiesca, J. Efren (Ecosistemas y Recursos Agropecuarios, 2022)
The study evaluated the chemical composition, dry matter degradability, methane (CH4) and carbon dioxide (CO2) production in mixed silage. Micro silos of King grass CT-115 were made with the inclusion of 20, 30 and 40% of Clitoria ternatea adding 5.0% molasses and 0.5% phosphoric acid. After 40 days of fermentation, dry matter (DM), crude protein (PC), neutral detergent fiber (NDF), acid detergent fiber (ADF), pH, ammonia nitrogen (NA) and volatile fatty acids (VFA) were determined. The in vitro fermentation carried out measured dry matter degradability, CH4 and CO2 emissions at 24, 48 and 72h. The inclusion of Clitoria ternatea in the silages increased the content of DM and PC (P
Keywords: Chemical composition; micro-silos fermentation; forages; greenhouse gases